Influence of Sowing Seasons and Inter-plant Spacing on the Performance of Soybean [Glycine max (L) Merill] - Pallavi, M.; Shahana, Firdoz; Madhavi, B. (International Journal of Bio-resource and Stress Management, 2023)
Field experiments were conducted during kharif and rabi seasons of 2013 and 2013-14, respectively for two consecutive seasons at research farm of Regional Sugarcane and Rice Research Station, Rudrur to evaluate the effects of different cropping seasons and inter-plant spacing on performance of soybean genotypes. Higher seed yields were recorded during kharif season as compared to rabi season as lower thermal heat units were recorded during rabi season for both 50% flowering and maturity. Grain yield showed no significant difference under different inter-plant spacing. Branches plant-1 and clusters plant-1 showed significant variation under different inter-plant spacing and an inter-plant spacing of 10 cm recorded highest branches plant-1 and clusters plant-1. The number of pods plant-1 which is a decisive character for seed yield showed significant variation among different inter-plant spacing in both kharif season and rabi season and an inter-plant spacing of 10 cm recorded highest number of pods plant-1. Among genotypes Basar recorded highest grain yield during kharif season and JS-93-05 during rabi season. The kharif season crop recorded higher gross returns, net returns and B:C ratio when compared to rabi season crop. Among different spacings a spacing of 30×10 cm2 was economically feasible as it recorded highest B:C ratio. Hence cultivation of soybean during rabi season in Northern Telangana Zone is not advisable as it is not economically feasible.